2019
DOI: 10.1016/j.eclinm.2019.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Sex Composition of Older Siblings and Infant Mortality in India from 1992 to 2016

Abstract: BackgroundThis study examines associations between sex composition of older siblings and infant mortality by sex, to guide efforts to address excess female infant mortality in India.MethodsWe conducted a retrospective cross-sectional study of infant mortality in India using four waves of data from the nationally-representative National Family Health Survey, collected between 1992 and 2016 (unweighted N = 338,504 for children aged 1–5). We used sex-stratified multivariable logistic regression models to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The studies were published in a period between 1929 and 2020. Up to the 1980s, there were only thirteen publications [ 15 , 27 , 51 , 54 , 56 , 57 , 61 , 63 – 68 ], and the number increased to 21 in the 1980s [ 8 , 23 , 28 , 34 , 58 , 59 , 69 83 ], 46 in the 1990s [ 3 , 4 , 6 , 12 , 22 , 24 , 33 , 39 , 43 , 44 , 46 , 49 , 52 , 53 , 84 – 115 ], decreased to 30 in the 2000s [ 7 , 11 , 16 , 17 , 21 , 25 , 26 , 36 , 41 , 47 , 50 , 60 , 62 , 116 132 ], and reached 44 in the period between 2010 and 2020 [ 1 , 2 , 5 , 13 , 14 , 18 20 , 29 32 , 35 , 37 , 38 , 40 , 42 , 45 , 48 , 55 , 133 156 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies were published in a period between 1929 and 2020. Up to the 1980s, there were only thirteen publications [ 15 , 27 , 51 , 54 , 56 , 57 , 61 , 63 – 68 ], and the number increased to 21 in the 1980s [ 8 , 23 , 28 , 34 , 58 , 59 , 69 83 ], 46 in the 1990s [ 3 , 4 , 6 , 12 , 22 , 24 , 33 , 39 , 43 , 44 , 46 , 49 , 52 , 53 , 84 – 115 ], decreased to 30 in the 2000s [ 7 , 11 , 16 , 17 , 21 , 25 , 26 , 36 , 41 , 47 , 50 , 60 , 62 , 116 132 ], and reached 44 in the period between 2010 and 2020 [ 1 , 2 , 5 , 13 , 14 , 18 20 , 29 32 , 35 , 37 , 38 , 40 , 42 , 45 , 48 , 55 , 133 156 ].…”
Section: Resultsmentioning
confidence: 99%
“…Turke (1988) found that women with older daughters had a better reproductive outcome than those who had sons, and this positive reproductive outcome was enhanced further in families who had two older daughters. To elaborate, a recent study (N ¼ 338,504 for children aged 1-5) by Raj et al (2019) in India drew analogous conclusions; infants with two older sisters had lowered infant mortality in comparison to those with an older brother.…”
Section: Alloparenting By Siblings and Culturesmentioning
confidence: 89%
“…In addition, a number of these studies are based on data that are dated or are not nationally representative. Finally, despite prior research from India documenting effects of child sex on both birth spacing and child health outcomes in India (Chalasani & Rutstein, 2014;Edmeades et al, 2012;Raj et al, 2015Raj et al, , 2019Rutstein, 2005;Vilms et al, 2017), with girls being more vulnerable across issues, little analysis on the relationship between IPI and these child health outcomes has been conducted.…”
Section: Introductionmentioning
confidence: 99%